ESTIMATION VARIABILITY AND SOME GENETIC PARAMETERS FOR YIELD AND ITS COMPONENTS IN PEA GENOTYPES UNDER DIFFERENT PHOSPHOROUS LEVELS. - Samar A. Yako; Payman A. A. Zibari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to estimate variability and some genetic parameters for yield and yield components in pea (Pisum sativum L.) genotypes under different phosphorous levels. A field experiment was carried out at the field of Horticulture Department, College of Agricultural Engineering Sciences, Duhok University, on the 1st of November 2021. the experiment unites layout according to split-plot arrangement, the main plots include phosphorus levels (0, 18, 36, and 54 kg ha-1 P2O5 and the subplot represented the thirteen genotypes within RCBD. The results exhibited that phosphorus levels were highly significant for all traits except biological yield, also the genotypes show highly significant the with exception of harvest index, while the interaction between phosphorus levels and genotypes was highly significant for all studied traits except harvest index and pod length. The rate of 54 kg ha-1 P2O5 gave the highest value for the number of pods 281.359), length pod 3.94, 500 seed weight 86.54, biological yield 361.55, harvest index 10.82 and yield seed per plant 23.30. The local variety was superior in leaf area 808.08mm, length pod 10 cm, 500 seeds weight 25.369, also the genotype (1) gave the highest yield per plant 44.0367 kg ha-1 P2O5, for the interaction between genotypes and phosphorus levels of genotype (2).